Geometric uncertainty analysis of MLC tracking for lung SABR. (30th November 2020) - Caillet, Vincent; Zwan, Benjamin; Briggs, Adam; Hardcastle, Nicholas; Szymura, Kathryn; Prodreka, Alexander; O'Brien, Ricky; Harris, Ben E; Greer, Peter; Haddad, Carol; Jayamanne, Dasantha; Eade, Thomas; et al.
Abstract: Purpose. The purpose of this work was to report on the geometric uncertainty for patients treated with multi-leaf collimator (MLC) tracking for lung SABR to verify the accuracy of the system. Methods. Seventeen patients were treated as part of the MLC tracking for lung SABR clinical trial using electromagnetic beacons implanted around the tumor acting as a surrogate for target motion. Sources of uncertainties evaluated in the study included the surrogate-target positional uncertainty, the beam-surrogate tracking uncertainty, the surrogate localization uncertainty, and the target delineation uncertainty. Probability density functions (PDFs) for each source of uncertainty were constructed for the cohort and each patient. The total PDFs was computed using a convolution approach. The 95% confidence interval (CI) was used to quantify these uncertainties. Results. For the cohort, the surrogate-target positional uncertainty 95% CIs were ±2.5 mm (−2.0/3.0 mm) in left-right (LR), ±3.0 mm (−1.6/4.5 mm) in superior–inferior (SI) and ±2.0 mm (−1.8/2.1 mm) in anterior–posterior (AP). The beam-surrogate tracking uncertainty 95% CIs were ±2.1 mm (−2.1/2.1 mm) in LR, ±2.8 mm (−2.8/2.7 mm) in SI and ±2.1 mm (−2.1/2.0 mm) in AP directions. The surrogate localization uncertainty minimally impacted the total PDF with a width of ±0.6 mm. The target delineation uncertainty distribution 95% CIs were ±5.4 mm. For the total PDF, the 95% CIs were ±5.9 mm (−5.8/6.0 mm) in LR, ±6.7 mm (−5.8/7.5 mm) in SI and ±6.0 mm (−5.5/6.5 mm) in AP. Conclusion. This work reports the geometric uncertainty of MLC tracking for lung SABR by accounting for the main sources of uncertainties that occurred during treatment. The overall geometric uncertainty is within ±6.0 mm in LR and AP directions and ±6.7 mm in SI. The dominant uncertainty was the target delineation uncertainty. This geometric analysis helps put into context the range of uncertainties that may be expected during MLC tracking for lung SABR (ClinicalTrials.gov registration number: NCT02514512).